1997
DOI: 10.1007/s002180050210
|View full text |Cite
|
Sign up to set email alerts
|

Neutron halos in heavy nuclei-relativistic mean field approach

Abstract: Assuming a simple spherical relativistic mean field model of the nucleus, we estimate the width of the antiproton-neutron annihilation (Γ n ) and the width of antiproton-proton (Γ p ) annihilation, in an antiprotonic atom system. This allows us to determine the halo factor f , which is then discussed in the context of experimental data obtained in measurements recently done on LEAR utility at CERN. Another quantity which characterizes the deviation of the average nuclear densities ratio from the corresponding … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…At large distance and for r ≃ 0, the f 7/2 one-neutron state strongly dominates all the other ones. This clearly indicates that the halo is a single particle effect in this nucleus, which confirms earlier results obtained with Skyrme forces [1] and with the relativistic mean field theory [3]. The middle plot of the lowest row in Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…At large distance and for r ≃ 0, the f 7/2 one-neutron state strongly dominates all the other ones. This clearly indicates that the halo is a single particle effect in this nucleus, which confirms earlier results obtained with Skyrme forces [1] and with the relativistic mean field theory [3]. The middle plot of the lowest row in Fig.…”
Section: Resultssupporting
confidence: 90%
“…In particular, it has been found that several neutron rich nuclei display a neutron skin or even a neutron 'stratosphere' called the neutron halo. Such properties of neutron distributions have been predicted by the asymptotic density model [2], the relativistic mean field theory [3], and Hartree-Fock calculations with Skyrme forces [1].…”
Section: Introductionmentioning
confidence: 99%
“…The number of nuclei with one fewer neutron or proton is proportional to the quantities Im(δp n )ρ n or Im(δp p )ρ p , respectively, integrated over the region where the annihilation process takes place. Thus, approximately, one can estimate theoretically the halo factor as [37,48] …”
Section: Some Aspects Of the Methods And Results In Antiprotonic mentioning
confidence: 99%
“…Therefore, at the present stage of this research we concentrate on the HFB method. We hope that in future works our experimental data will allow to discriminate between different approaches [64] modelling the nuclear periphery.…”
Section: A Nuclear Periphery From Hfb Calculationsmentioning
confidence: 99%